Esfaqueamento no púlpito: o comércio e suas elites em Cachoeira do Sul na segunda metade do séc. XIX (1845-1865) - Fagundes, Rosicler Maria Righi (Universidade do Vale do Rio do Sinos, 2009)
This inquiry is dedicated to study the mercantile elites of Cachoeira do Sul, in the period from 1845 to 1865. The study about merchants in the Imperial period in Rio Grande do Sul is a subject still very little explored by the historiography. That is why we will seek to understand the actions and strategies adopted for the insertion of this group in the eight hundredth’s society, using the path of the merchant Antonio Vicente da Fontoura as a guideline. In order to understand the subjects belonging to the mercantile elites, the main source used was the post-mortem inventories, as well as the documentation found in the city council of Cachoeira do Sul, crime processes and private sources. However, if occupying a place in the mercantile elite meant having economical power, that was not enough to maintain oneself on the top. Therefore, there was the need to weave vertical and horizontal networks. From that interaction with the pairs and the subordinates the mercantile elites were confirmed in the power and inse
Keywords: estratégias; redes sociais; trajetórias; elites mercantis; paths; social networks; strategies; mercantile elites; Ciências Humanas